Judicial activism and the American election process - Laidler, Paweł (Politologia, 2020)
This article analyses the phenomenon of judicial activism in the American electoral process. It tries to estimate whether the political system of the United States of America has become hostage to the law-making role of the judiciary, which actively controls the compliance of election laws with the Constitution, thus drawing courts into purely political processes, or whether the nature of the disputes settled by judges rather makes it impossible for them to avoid being influenced by and influencing issues of a political nature. The article analyses various legal acts and court decisions, mostly concerning the current status of federal campaign finance in the United States, and demonstrates that more spheres traditionally reserved for other branches of government are being appropriated by the judicial branch.